New trends in non-invasive study of human skin microcirculation. A descriptive review - Fedorovich, A. A.; Korolev, A. I.; Ososkov, V. S.; Samatova, K. S.; Drapkina, O. M. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2025)
The aim of this descriptive review is to analyze the current state and further development of a new direction in functional diagnostics — non-invasive study of human skin microcirculation. The review considers the most frequently used non-invasive methods for research studying human skin microcirculation. The diagnostic potential of various devices is assessed taking into account the physical characteristics of their functioning and the skin microcirculation angioarchitectonics. The article considers the main directions of improvement of computer videocapillaroscopy, laser Doppler flowmetry and photoplethysmography methods, which are based on modern computer technologies and microelectronics. The main trends in this direction are miniaturization of devices, remote data transmission and the use of modern methods of automatic data analysis. A completely new method of obtaining physiological information is the analysis of a video plethysmography records using a conventional webcam. The method is based on the analysis of changes in the contrast of pixels during video recording of the skin surface, where the transitional capillary zones are located, blood flow changes in which lead to a change in the contrast of the pixels recorded by a standard webcam.